Iron deficiency anemia in children: a challenge for public health and for society - Coutinho, Geraldo Gaspar Paes Leme; Goloni-Bertollo, Eny Maria; Bertelli, Érika Cristina Pavarino (São Paulo Medical Journal, 2005)
Iron deﬁciency anemia is the principal nutritional dearth in the world, and it especially affects children and pregnant women in developing countries. This paper presents a survey of the literature in this area, with the aim of providing a brief overview regarding the occurrence of iron deﬁciency anemia in Brazil. The article describes the etiology of the disease, the risk groups, the high prevalence of anemia in several areas of Brazil, and also the consequences of iron deﬁ- ciency in children. The paper also shows some ways to control iron deﬁciency anemia and some intervention programs applied in Brazilian cities for curing and/or preventing this disease. The article concludes by emphasizing the need to establish strategies and treatments in our country that are based on a policy that brings together not only governmental administration but also all the community.